(untitled) (Research, Society and Development, 2022)
Introduction: Water birth is progressively expanding in several countries around the world with availability to low obstetric risk women. Objective: To understand the experience of Nurses Specialists in Maternal Health and Obstetrics about their clinical practice, in the assistance to the woman who planned and experienced the execution of the water birth, in order to contribute to the clinical practice of the professionals who are involved both in the preparation for childbirth, as well as in labor and water birth. Method: Qualitative study where 12 Nurses Specialists in Maternal and Obstetric Health were interviewed about their experiences in assisting births in water in Portugal, through the non-probabilistic sampling technique - Snowball. Data collection took place in October 2015, through individual interviews. Results: The participants’ narratives were grouped into three categories: 1 - Water Birth Assistance as an Exciting Experience; 2 - Preparation for water birth: greater autonomy for women and nurses as spectators and 3 - Water birth and the smooth transition of the newborn. Conclusion: This study indicated that through the experience of Obstetric Nurses it was possible to look at water birth as a natural process of parturition and birth, also as an event that does not need intervention in most cases, the preparation of both the woman and the partner was key to an exhilarating experience and a smooth newborn transition.